Analysis of Digital Marketing and Customer Relationship Marketing on Customer Repurchase Interest in Café Kisah Kita Ngopi through Electronic Word Of Mouth - Ernantyo, Yosef evandro; Timotius Febri C.W. Sutrisno (Universitas Ciputra Surabaya, 2024)
Purpose: The high competition in the cafe business causes the Story of Kita Ngopi Café to continue to look for solutions so that interest in repeat purchases continues to occur. The objectives of this research are: 1). To find out and analyze digital marketing which has a significant influence on the Electronic Word of Mouth Café Kita Ngopi Story 2). To find out and analyze customer relationship marketing which has a significant influence on Electronic Word of Mouth Café Kita Ngopi Story 3). To find out and analyze Electronic Word of Mouth which has a significant effect on repurchase interest in Café Story Kita Ngopi 4). To find out and analyze digital marketing which has a significant influence on repurchase interest in Café Story Kita Ngopi 5). To find out and analyze customer relationship marketing which has a significant influence on repurchase interest in Café Story Kita Ngopi. Methodology: Research subjects are coffee connoisseurs in Surabaya and Sidoarjo who have been customers at Café KitaNgopi during the data collection period, who can be contacted to take the time to fill out the questionnaire and recommend other community members as respondents. Hypothesis testing will be carried out using the Structural Equation Modeling method using PLS. The results of the research show that 1) Digital Marketing has a significant positive effect on Electronic word of Mouth at the Story Kita Ngopi Cafe 2) Customer Relationship Marketing has a positive and significant effect on the Electronic word of Mouth at the Story Kita Ngopi Cafe 3) Electronic word of Mouth has no significant effect on repurchase interest at the Story Kita Ngopi Cafe 4) Digital Marketing has a significant positive effect on repurchase interest at the Story Kita Ngopi Cafe 5) Customer Relationship Marketing has a positive and significant effect on repurchase interest at the Story Kita Ngopi Cafe Practical Implication: For business people in the food and beverage sector who are running a cafe business, it is necessary to examine other variables that cause satisfaction and purchase retention from their customers